Whole Brain Imaging with Serial Two-Photon Tomography - Amato, Stephen P.; Pan, Feng; Schwartz, Joel; Ragan, Timothy M. (Frontiers in Neuroanatomy, 2016)
Imaging entire mouse brains at submicron resolution has historically been a challenging undertaking and largely confined to the province of dedicated atlasing initiatives. The has limited systematic investigations into important areas of neuroscience, such as neural circuits, brain mapping and neurodegeneration. In this paper, we describe in detail Serial Two-Photon (STP) tomography, a robust, reliable method for imaging entire brains with histological detail. We provide examples of how the basic methodology can be extended to other imaging modalities, such as optical coherence tomography, in order to provide unique contrast mechanisms. Furthermore we provide a survey of the research that STP tomography has enabled in the field of neuroscience, provide examples of how this technology enables quantitative whole brain studies, and discuss the current limitations of STP tomography-based approaches